AUSTRALIA'S MEMBERSHIP IN THE ASSOCIATION OF SOUTHEAST ASIAN NATIONS IN RELATION WITH HUMAN RIGHTS POLICIES - Danielle Putri Ratu (Padjadjaran Journal of International Law, 2020)
Abstract Australia, as one of the first dialogue partners of ASEAN has been one of the subjects in a continuous discussion over the need to further integrate Australia within ASEAN and therefore making Australia as one of the Member States of ASEAN. This is accompanied with the idea of advancing the partnership, bearing in mind the many accomplishments that the partnership have yielded. However, there are varying complex issues at hand regarding Australia's membership. A membership would mean compliance with the ASEAN Charter, where it is found to be difficult for Australia in fulfilling all the needed requirements and may restrict Australia in certain fields of concern, one of which is human rights policies. ASEAN is known for its ASEAN Way, which is a non-interference and consensus based method in resolving issues and maintaining peace and security, that includes human rights. This has generated criticism in ASEAN's inability to protect human rights while also failing to hold accountability of human rights law violations. This is also due to the inadequate legal instruments that does not provide a proper protection and prevention of human rights violations. In relation to Australia's membership, this would create a conflicting issue since there are several differences between Australia and ASEAN regarding human rights policies, along with its values. As there seems to be no urgency to integrate Australia as a member into ASEAN, therefore membership is not needed to avoid unwanted conflict and partnership between the party can still be built as dialogue partners. Keywords: ASEAN, Australia, Human Rights Law Abstrak Australia sebagai salah satu negara pertama yang menjadi dialogue partner ASEAN seringkali menjadi subjek diskusi mengenai keinginan untuk mengintegrasikan Australia dengan ASEAN dan kemudian menjadikan Australia sebagai salah satu anggota dari ASEAN. Hal ini disertai pula dengan ide untuk meningkatkan kerja sama yang telah ada, mengingat berbagai keberhasilan yang telah dihasilkan dari padanya. Namun, terdapat beberapa permasalahan yang ada mengenai keanggotaan Australia. Keanggotaan akan berarti kepatuhan terhadap Piagam ASEAN, dimana akan sulit bagi Australia untuk memenuhi semua persyaratan yang ada dan memunculkan kemungkinan bagi Australia untuk terhalangi di beberapa aspek, yang salah satunya merupakan hukum hak asasi manusia. ASEAN itu sendiri dikenal dengan ASEAN Way, yang merupakan suatu metode yang didasarkan dengan non-intervensi dan konsensus dalam menyelesaikan masalah dan dalam menjaga keamanan dan kedamaian yang juga berkaitan dengan hak asasi manusia. Hal ini telah memunculkan kritik terhadap ketidakmampuan ASEAN dalam melindungi hak asasi manusia dan meminta pertanggungjawaban atas pelanggaran hukum hak asasi manusia. Hal ini juga dikarenakan instrumen hukum yang tidak memadai karena tidak menyediakan perlindungan dan pencegahan yang cukup terhadap pelanggaran hukum hak asasi manusia. Dihubungkan dengan keanggotaan Australia, maka hal ini akan memunculkan permasalahan yang bertabrakan dimana adanya perbedaan antara Australia dan ASEAN mengenai hukum hak asasi manusia, beserta nilai-nilai yang dipegang. Oleh karena tidak adanya urgensi untuk keanggotaan Australia, maka keanggotaan itu tidak diperlukan demi menghindari konflik yang tidak diinginkan dan kerjasama antara keduanya masih dapat dibangun dengan dasar sebagai dialogue partner. Kata Kunci: ASEAN, Australia, Hukum Hak Asasi Manusia